Electronic archive of enterprise documents - Мазур, В. І.; Шпак, Ю. І.; Мазур, О. Ю.; Давиденко, В. В. (Problems of Informatization and Control, 2005)
The basic principles of documents’ electronic warehouse creation are considered. The way of solving the problem by means of software developed by the authors of article is proposed